Enhancing the quality of homestay services in Lembah Oya to support sustainable tourism development in Selopamioro - Kiki Rizki Makiya; Dwiyono Rudi Susanto; Fitria Noviati; Eko Haryanto (Universitas Muhammadiyah Magelang, 2024)
Homestays provide accommodation for tourists who visit or purchase tour packages offered in tourist villages. The homestay in Selopamioro Village is part of the Oya Valley Homestay Association. Despite the existence of a community association, its governance system, institutions, service standards, and readiness in terms of administration and available facilities still do not meet homestay standards. The aim of this activity is to provide training and assistance to homestay managers to increase governance capacity and the quality of services provided to staying tourists, thereby supporting the sustainable development of green tourism in Selopamioro. The methods used include: 1) Field observations and interviews to identify the problems faced, 2) Program socialization, 3) Training and mentoring, and 4) Providing amenities. The results of this activity include an increase in governance and administration capacity, improved institutions, enhanced ability to serve guests, and provision of facilities such as bed sheets, blankets, and bed runners for each homestay room, as well as name boards and directions to make it easier to locate the homestay.